1994
DOI: 10.1016/0928-8244(94)90063-9
|View full text |Cite
|
Sign up to set email alerts
|

The effects of extracellular slime from Staphylococcus epidermidis on phagocytic ingestion and killing

Abstract: Extracellular slime (Ecs) from three strains of Staphylococcus epidermidis was prepared and added to fresh suspensions of polymorphonuclear neutrophils. Phagocytic ingestion and killing of opsonised and unopsonised S. epidermidis strains was assessed over time using slide preparations stained by the Gram's method and microbiological culture. Both phagocytic ingestion and killing were inhibited. Investigation as to one possible mechanism of action of Ecs on phagocytes was performed using 1 mu polystyrene sphere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…Beginning in the 1980s, several reports were published providing evidence for that function [2830]. Recent research has given more mechanistic insight, showing that S. epidermidis biofilms protect from neutrophil-dependent killing by complement inactivation via prevention of the deposition of C3b and immunoglobulin G (IgG) [31].…”
Section: Virulence Factors Of S Epidermidismentioning
confidence: 99%
“…Beginning in the 1980s, several reports were published providing evidence for that function [2830]. Recent research has given more mechanistic insight, showing that S. epidermidis biofilms protect from neutrophil-dependent killing by complement inactivation via prevention of the deposition of C3b and immunoglobulin G (IgG) [31].…”
Section: Virulence Factors Of S Epidermidismentioning
confidence: 99%
“…Once bound to the biomaterial, the second step involves the formation of bio®lm. Bio®lm, or its components, have been shown to protect S. epidermidis from antibiotics [37,45], phagocytes [14,38] and inhibit other immune-related activities [10,42]. The end result is that the bacteria are allowed to persist and be shed into the blood for prolonged periods of time.…”
Section: Introductionmentioning
confidence: 99%
“…Biofilms are highdensity bacterial consortia, adherent to a surface, in which bacteria are embedded in a heterogeneous bacterium-derived matrix. Early studies already found evidence that biofilm-forming S. epidermidis strains are less susceptible to host innate immune effector mechanisms than non-biofilm-forming strains (19,32,33). It is assumed that in conjunction with the severely reduced susceptibility of biofilm-forming S. epidermidis to antimicrobials, immune escape mechanisms contribute essentially to the chronic persistent course of implant-associated S. epidermidis infections (6,36).…”
mentioning
confidence: 99%